2020
DOI: 10.1186/s12939-020-01182-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal height associated with cesarean section. A cross-sectional study using the 2014–2015 national maternal-child health survey in Guatemala

Abstract: Background: Socioeconomic status is associated with cesarean section (CS). Maternal height, however, may be another related factor to CS. In Guatemala, a quarter of women between 15 and 49 years of age are shorter than 145 cm. Therefore, this study aims to examine the association of maternal height with cesarean section in Guatemala. Methods: We carried out a secondary analysis study using data from the 2014-15 Guatemalan national maternal and child health survey-9542 mothers aged 15-49 and 12,426 live births … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
1
13
2
Order By: Relevance
“…Another important factor that contributes to the association between short maternal height and CS is nutritional status. Shorter women were more likely to be overweight or obese than taller women, 21 40 and obesity has been linked to increase in CS. 21 41 Furthermore, our study found that higher odds of CS among mothers who were overweight/obese before pregnancy and had a higher risk related to height and pregnancy related complications than those among mothers' with normal weight.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Another important factor that contributes to the association between short maternal height and CS is nutritional status. Shorter women were more likely to be overweight or obese than taller women, 21 40 and obesity has been linked to increase in CS. 21 41 Furthermore, our study found that higher odds of CS among mothers who were overweight/obese before pregnancy and had a higher risk related to height and pregnancy related complications than those among mothers' with normal weight.…”
Section: Discussionmentioning
confidence: 96%
“…Shorter women were more likely to be overweight or obese than taller women, 21 40 and obesity has been linked to increase in CS. 21 41 Furthermore, our study found that higher odds of CS among mothers who were overweight/obese before pregnancy and had a higher risk related to height and pregnancy related complications than those among mothers' with normal weight. 21 Therefore, obesity prior to or during pregnancy in short or very short mothers may cause labour to be prolonged, and triggers a need for CS.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Actively addressing exclusion requires going beyond health system financing to develop policies aimed at including afro-descendants, indigenous peoples, and others who live in poverty and/or are geographically excluded from accessing health facilities, while addressing health worker capacities and provider incentives. Obstetric violence continues to be a central issue in the region: Roldán, Grajeda & Pérez found that Cesarean section rates in Guatemala were high and above international recommendations, with the bulk of these procedures being performed in shorter women [ 12 ]. In the country, indigenous and poor women tend to be much shorter than their non-indigenous counterparts, which points towards the overuse of a medical procedure in a traditionally marginalized population group that already faces compounding factors that limit the use of their agency when it comes to deciding how and when to give birth.…”
mentioning
confidence: 99%